Psychological Characteristics of Gifted Personality - E V Belovol; M A Rushina (Peoples' Friendship University of Russia (RUDN University), 2014)
This paper presents the theoretical concepts of a gifted personality. The peculiarities of talent diagnostics as a multi-level system are considered in the article. Also the psychometric model of identifying talent as personal potential is proposed.